Extreme conformational diversity in human telomeric DNA - Lee, J. Y. (National Academy of Sciences, 2005)
DNA with tandem repeats of guanines folds into G-quadruplexes made of a stack of G-quartets. In vitro, G-quadruplex formation inhibits telomere extension, and POT1 binding to the single-stranded telomeric DNA enhances telomerase activity by disrupting the G-quadruplex structure, highlighting the potential importance of the G-quadruplex structure in regulating telomere length in vivo. We have used single-molecule spectroscopy to probe the dynamics of human telomeric DNA. Three conformations were observed in potassium solution, one unfolded and two folded, and each conformation could be further divided into two species, long-lived and short-lived, based on lifetimes of minutes vs. seconds. Vesicle encapsulation studies suggest that the total of six states detected here is intrinsic to the DNA. Folding was severely hindered by replacing a single guanine, showing only the shortlived species. The long-lived folded states are dominant in physiologically relevant conditions and probably correspond to the parallel and antiparallel G-quadruplexes seen in high-resolution structural studies. Although rare under these conditions, the short-lived species determine the overall dynamics because they bridge the different long-lived species. We propose that these previously unobserved transient states represent the early and late intermediates toward the formation of stable G-quadruplexes. The major compaction occurs between the early and late intermediates, and it is possible that local rearrangements are sufficient in locking the late intermediates into the stably folded forms. The extremely diverse conformations of the human telomeric DNA may have mechanistic implications for the proteins and drugs that recognize G-rich sequences.